Association between maternal postpartum depression and children's physical growth in early childhood: a birth cohort study - He, Qiong; Cheng, Gang; He, Simin; Tian, Gang; Xie, Xiaowei; Jiang, Ni; Min, Xianying; Li, Chao; Li, Rui; Shi, Yan; Zhou, Tong; Yan, Yan (Frontiers in Pediatrics, 2023)
Background: Untreated maternal postpartum depression (PPD) has consequences for children's physical growth, but no published study has evaluated changes in this effect over time. Here we therefore aimed to evaluate the dynamic effects of PPD on the physical growth of children in a prospective birth cohort.Methods: Between 2015 and 2019, 960 mother-child pairs in Changsha, China were followed up when the child was aged 1-48 months. Data were obtained through household surveys. The mothers' depressive symptoms were measured using the Edinburgh Postpartum Depression Scale (EPDS) at 1 month postpartum. Linear mixed models were used to examine the changes in the association of PPD and EPDS scores with physical growth in six different age groups of children between 1 and 48 months.Results: A total of 604 mother-child pairs completed the follow-up, and 3.3% of mothers reported PPD. No associations were found between PPD and weight or height growth at any age. While EPDS scores were associated with weight gain (β=-0.014, 95%CI (-0.025, -0.002), P=0.024) and height growth (β=-0.044, 95%CI (-0.084, -0.004), P=0.030) rates at 1-3 months, no associations were found in older children.The number of mothers who reported PPD was relatively small, and the measurement of PPD was not continuously taken.After adjustments for confounders, no dynamic association was found between PPD and children's weight and height growth. EPDS scores, in contrast, did negatively affect children's weight and height growth at age 1-3 months, but this effect was not long-lasting.